The Utility of Endoscopic Ultrasound Guided Fine Needle Aspiration in the Diagnosis of Infectious Diseases—Report of Three Cases - Mauro Ajaj Saieg; Felipe Yazawa; Manuela Horta; Lucio G. Rossini; Mabel Tatty Medeiros Fracassi; Fabíola Del Carlo Bernardi (Case Reports in Infectious Diseases)
Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is a fast and minimally invasive methodology with a crucial impact on patients’ management. It has an important and established role in the diagnosis and staging of mediastinal and abdominal malignancies, but little is discussed in the literature on the usefulness of this technique in the diagnosis of infectious diseases. In the current report, we present three different cases where EUS was essential for reaching the diagnosis of tuberculosis and paracoccidiodomicosis in cases otherwise seen as malignant. In conclusion, EUS was successful not only in obtaining enough cells for morphological analysis, but also for the production of cell blocks and assessment of the presence of the microorganisms by special stains. EUS allied to fine needle biopsy was an important tool in determining diagnoses of enlarged lymph nodes, revealing the diagnosis of infectious diseases in cases otherwise seen as malignant. The wide use of this methodology in cases such as those reported here cannot only rule out malignancy, but also aid critically ill patients by installing early proper therapy without the need for aggressive interventions.